2016
DOI: 10.1080/08037051.2016.1182419
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension is strongly associated with false-positive bicycle exercise stress echocardiography testing results

Abstract: Hypertension is a risk factor for false-positive stress exercise echocardiographic results in patients with known or suspected coronary artery disease. Presence of hypertension was associated with 17.6-fold elevated risk of false-positive results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…5,7,11,12,14,15,18,19 Hypertensive response to exercise was considered the main factor responsible for an FP-ESE result in six studies. 4,8,10,11,13,16 Exercise-induced left ventricular wall motion (LVWM) abnormalities in patients with hypertensive response to exercise have been primarily ascribed to an abnormally high rate-pressure product, resulting in subendocardial ischemia secondary to a mismatch between myocardial oxygen supply and demand.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5,7,11,12,14,15,18,19 Hypertensive response to exercise was considered the main factor responsible for an FP-ESE result in six studies. 4,8,10,11,13,16 Exercise-induced left ventricular wall motion (LVWM) abnormalities in patients with hypertensive response to exercise have been primarily ascribed to an abnormally high rate-pressure product, resulting in subendocardial ischemia secondary to a mismatch between myocardial oxygen supply and demand.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 17 studies were thus included in the analysis, totaling 5174 individuals (Table 1). [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] With regard to the RoB, the NIH quality rating was estimated as good for 10 studies and fair for 7 studies (Supplemental Table 1, http://links.lww.com/ JCM/A563).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, relationship between hypertensive response to exercise and FST also reflects that exercise-induced increased afterload affects endocardial function through impaired vascular-ventricular interaction [ 22 ]. Some previous studies showed that hypertensive response was linked to FST without CAD [ 10 , 23 ]. According to our study results, hypertensive response due to increased arterial stiffness [ 2 , 24 , 25 , 26 ] is associated with FST, but hypertensive responses at a younger age can be linked to augmentation of SV due to vigorous LV contraction [ 24 ].…”
Section: Discussionmentioning
confidence: 99%